JURIDICAL ANALYSIS OF THE IMPLEMENTATION OF PASSENGER AND CARGO SHIP SAFETY EQUIPMENT STANDARDS IN THE BATAM PORT AREA - Rachmat Hidayat; Laily Washliati; Parameshwara (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
Shipping safety is a fundamental aspect of sea transportation operations, especially for passenger and cargo vessels operating in strategic areas such as Batam Port. The 1974 International Convention for the Safety of Life at Sea (SOLAS) as a global legal instrument has been ratified by Indonesia and adopted into the national legal system through Law Number 17 Year 2008 on Shipping. However, the level of marine accidents that still occur and the findings of non-standard safety equipment on some ships indicate problems in the implementation of legal norms in the field. This study aims to analyze the legal regulation and implementation of safety equipment standards for passenger and cargo vessels in Batam Port area based on 1974 SOLAS Convention, as well as to identify obstacles and solutions for its implementation. The method used is legal research with normative juridical and empirical juridical approaches. Data were obtained through legal document studies and in-depth interviews with officials of the Batam Harbor and Port Authority Office (KSOP) and shipping industry players. The results showed that normatively, Indonesia already has adequate legal arrangements and is in line with international standards. However, at the implementation level, there are still normative (unsynchronized technical regulations), structural (limited human resources and facilities at KSOP), and legal culture (low awareness of business actors) obstacles. Therefore, it is necessary to increase supervisory capacity, harmonize national regulations with international practices, as well as legal education and shipping safety campaigns to realize effective and equitable implementation of ship safety equipment